LEARNING DESIGN OF ENGLISH FOR BROADCAST THROUGH COMMUNICATIVE LANGUAGE TEACHING (CLT) APPROACH - Heru Saputra (Edulitics (Education, Literature, and Linguistics) Journal, 2018)
English broadcast should be conducted in a communicative language to maintain the existence and quality of campus radio. Based on the facts found, the broadcasters of IAIN Salatiga campus radio do not come from the Department of English Education, which then make them difficult in doing English broadcast and it needs solution. Empowerment is done on qualitative research; with the subjects are twenty (20) broadcasters on IAIN Salatiga campus radio. The data collection is done in three ways, namely: observation, questionnaire and Focus Group Discussion (FGD). From the data obtained, there are facts that 100% of the broadcasters have never experienced English language training for Broadcast, 80% get difficulties in doing communicative English broadcasts, and 100% are very often to find certain things to broadcast. The design of English learning for Broadcast is as follows: viewing factual conditions, learning by approach of Communicative Language Teaching (CLT), and output (implementation of communicative English in broadcasting) Keywords: Design, English Broadcast, ESP, CLT, Empowerment